An integrated 3D GIS-based method for estimating the urban potential of BIPV retrofit of façades. (November 2020) - Saretta, Erika; Caputo, Paola; Frontini, Francesco
Graphical abstract: Highlights: A novel 3D GIS method for assessing BIPV retrofit potential of façades is developed. The method combines different datasets to compute an integrated urban analysis. A Swiss residential urban area with multi-family buildings is used as case study. Increasing data accuracy affects urban BIPV retrofit potential of façades. Retrofitted BIPV façades have a crucial role, especially for winter energy balance. Abstract: To foster urban energy transition needed to limit the growing climate change' effects, the urban BIPV retrofit of façades can play a significant role thanks to the transformation of the existing energy-intensive building sector into an efficient energy producer. However, currently, there is a lack of tools for the evaluation of such potential mainly because it relies on several fragmented and heterogeneous urban data. Nevertheless, to exploit the not-negligible contribution of retrofitting façades with BIPV in urban energy transition, the assessment of this potential at the urban level should be considered. Therefore, this paper presents a novel integrated 3D GIS-based methodology for the evaluation of this potential, especially for the Swiss context and multi-family house buildings by combining data for the evaluation of the envelope retrofit potential and by increasing the accuracy of the assessment of the BIPV façade potential beyond typical LOD2. Moreover, it includes GIS-based tools for evaluating the BIPV façade potential, the energy retrofit potential of envelopes, and the annual and seasonal urban energy balance. Finally, implementation' results show that increasing the urban data' accuracy can significantly affect the urban BIPV retrofit potential of façades, thus providing new crucial information for energy planning.